Dynamic compressive properties of seawater coral aggregate concrete (SCAC) reinforced with mono or hybrid fibers. (18th July 2022) - Wang, Zhenbo; Li, Pengfei; Han, Yudong; Hao, Rusheng; Liu, Weikang
Highlights: Split Hopkinson pressure bar test was conducted to investigate the dynamic compressive response of mono and hybrid fiber SCAC. The distinct strain rate hardening effects of PVA fiber and hybrid fiber SCAC were clarified. A fitting model describing the relationship between DIF and strain rate was proposed to quantify the influence of different fibers. The failure mechanism of PVA fiber and steel fiber at different strain rates were analyzed. Abstract: Seawater coral aggregate concrete (SCAC) has shown particular advantages in controlling costs and curbing construction periods in offshore island and reef construction. However, with increasing strength of SCAC, its static and dynamic mechanical brittleness increases significantly. In this study, flexible fiber (polyvinyl alcohol fiber) and rigid fiber (steel fiber) were blended in SCAC to improve the strength, toughness, and dynamic performance of SCAC.A split Hopkinson pressure bar (SHPB) system with 75 mm diameter was used to test the dynamic mechanical response of SCAC reinforced with mono or hybrid fibers at different strain rates. The results show that the compressive stress–strain curves of SCAC demonstrated a pronounced strain rate hardening effect, and the addition of fiber significantly reduced the embrittlement at high strain rate. Particularly, the dynamic strength and DIF of mono polyvinyl alcohol (PVA) fiber SCAC increased with quasi-static strength, but the strengthening efficiency of PVA fiber decreased at high strain rate. Hybrid PVA-steel fiber made SCAC strain rate hardening effect occurred earlier, endowing higher dynamic compressive strength and DIF. The dissipated energy densities of mono PVA fiber SCAC increased with strain rates, but the increase slowed with higher strain rates. Adding steel fiber greatly improved the dissipated energy density of SCAC, and this increase effect initially enhanced before decreasing as strain rate increased. At low and medium strain rates, hybrid fiber SCAC failure were mainly due to slippage or pullout of PVA and steel fibers. At high strain rate, PVA fiber rupture or the plastic deformation and pullout of steel fiber were responsible for the strengthening and toughening effect, which made the damage degree of hybrid fiber SCAC superior to SCAC with mono PVA fiber or without fiber.